AN INTELLIGENT TARGET RECOGNITION SYSTEM BASED ON PERIODOGRAM FOR PULSED RADAR SYSTEMS - Avci, Engin; Turkoglu, Ibrahim (Gazi Univ, 2005)
In this study, a pattern recognition system is developed for automatic classification of the radar target signals. For feature extraction which is an important subset of the pattern recognition system, a new method which is based on periodogram power spectral density and intelligent classifier is proposed. Artificial neural network and adaptive network based fuzzy inference system were used as an intelligent classifier respectively. Radar signals were obtained from pulse radar system for various targets. According to developed feature extraction method, the classifier performances were evaluated with radar signals on the target recognition.
Keywords: Radar target classification; power density; pulsed radar; pattern recognition